FTIR/PCA study of propanol in argon matrix: the initial stage of clustering and conformational transitions - Doroshenko, Iryna; Balevicius, Vytautas; Pitsevich, George; Aidas, Kestutis; Sablinskas, Valdas; Pogorelov, Valeriy (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
FTIR spectra of 1-propanol in an argon matrix were studied in the range 11 to 30 K. Principal component analysis of dynamic FTIR spectra and nonlinear band shape fitting has been carried out. The peaks of monomer, open dimer, mixed propanol-water dimer and those of higher H-bond clusters have been resolved and analyzed. The attribution of certain FTIR peaks has been supported by proper density functional theory calculations. Analyzing dependences of the integral band intensities of various aggregates on temperature it has been deduced that in the initial stage of clustering monomers and dimers are the basic building blocks forming higher H-bond clusters. The peaks assigned to two conformers of monomers and mixed propanol-water dimers were investigated processing the temperature dependences of their integral intensities in Arrhenius plot. The obtained values of 0.18 kJ∙mol–1 for propanol monomer and 0.26 kJ∙mol–1 for mixed dimer are well comparable with the energy differences between the global minimum conformation of 1-propanol (Gt) and some other energetically higher structures (Tt or Tg).